A visual laryngoscope combined with a fiberoptic bronchoscope improves intubation outcomes in patients with predicted difficult airways in thoracic surgery - Hui-Zhong Hu; Xiang-Xiang Cheng; Tao Zhang; Guang-Lei Zhang; Guan-Jun Zhang; Wei-Wei Wu; Ren-Hu Li (BMC Pulmonary Medicine)
Abstract Objective To study the clinical effectiveness of visual laryngoscopy combined with fiberoptic bronchoscopy-guided double-lumen endotracheal tube intubation in thoracic surgery patients with predicted difficult airways in thoracic surgery airways. Methods We randomly divided 162 patients with predicted difficult airways who required double-lumen tracheal intubation for thoracic surgery and randomly divided them into the video laryngoscopy group (Group VL, n = 54),fiberoptic bronchoscopy group (Group F, n = 54), and video laryngoscopy combined with fiberoptic bronchoscopy group (Group FVL, n = 54) according to the randomized number table method. Then, the success rate of the first intubation, the duration of intubation, the duration of positioning, the degree of exposure of the vocal cords (Cormack-Lehane grade), and the adverse reactions during intubation were recorded and analyzed. Results The success rate of first-time intubation was significantly higher in the FVL group than in the F and VL groups (92.6% vs. 87.0% vs. 53.7%, P < 0.001), and the time of intubation in the FVL group was significantly shorter than that in the VL and F groups [(26.22 ± 9.34) s vs. (42.35 ± 11.21) s vs. (46.78 ± 21.96) s, P < 0.001)]. The positioning time in the FVL group was significantly shorter than that in the F and VL groups [(83.76 ± 15.18) s vs. (102.72 ± 21.89) s vs. (145.41 ± 20.12) s, F = 144.896, P < 0.001)].The number of patients with Cormack-Lehane grades I-II was significantly lower in the FVL group and the VL group than in the F group (88.9% vs. 77.8% vs. 59.3%, P < 0.05).The incidence of postoperative sore throat was significantly lower in the FVL group and the F group than in the VL group (22.4% vs. 27.6% vs. 50%, P < 0.001). Conclusion In difficult airway patients with high airway risk indices who require double-lumen endotracheal intubation, visual laryngoscopy combined with fiberoptic bronchoscopy improved the success rate of first-time intubation and shortened the intubation and positioning time. Trial registration Chinese Clinical Trial Register (identifier: ChiCTR2300076304; Date of registration: September 29, 2023).